Discovery of novel replication proteins for large plasmids in cyanobacteria and their potential applications in genetic engineering - Ohdate, Kazuma; Sakata, Minori; Maeda, Kaisei; Sakamaki, Yutaka; Nimura-Matsune, Kaori; Ohbayashi, Ryudo; Hess, Wolfgang R.; Watanabe, Satoru (Frontiers in Microbiology, 2024)
Numerous cyanobacteria capable of oxygenic photosynthesis possess multiple large plasmids exceeding 100 kbp in size. These plasmids are believed to have distinct replication and distribution mechanisms, as they coexist within cells without causing incompatibilities between plasmids. However, information on plasmid replication Rep proteins (Rep) necessary for plasmid replication initiation in cyanobacteria is limited. Synechocystis sp. PCC 6803 hosts four large plasmids, pSYSM, pSYSX, pSYSA, and pSYSG, but Rep proteins for these plasmids, except for CyRepA1 on pSYSA, are unknown. Using Autonomous Replication sequencing (AR-seq), we identified two potential Rep genes in Synechocystis 6803, slr6031 and slr6090, both located on pSYSX. The corresponding Rep candidates, Slr6031 and Slr6090, share structural similarities with Rep-associated proteins of other bacteria and homologs were also identified in various cyanobacteria. We observed autonomous replication activity for Slr6031 and Slr6090 in Synechococcus elongatus PCC 7942 by fusing their genes with a construct expressing GFP and introducing them via transformation. The slr6031/slr6090containing plasmids exhibited lower copy numbers and instability in Synechococcus 7942 cells compared to the expression vector pYS. While recombination occurred in the case of slr6090, the engineered plasmid with slr6031 coexisted with plasmids encoding CyRepA1 or Slr6090 in Synechococcus 7942 cells, indicating the compatibility of Slr6031 and Slr6090 with CyRepA1. Based on these results, we designated Slr6031 and Slr6090 as CyRepX1 (Cyanobacterial Rep-related protein encoded on pSYSX) and CyRepX2, respectively, demonstrating that pSYSX is a plasmid with "two Reps in one plasmid". Furthermore, we determined the copy number and stability of plasmids with cyanobacterial Reps in Synechococcus 7942 and Synechocystis 6803 to elucidate their potential applications. The novel properties of CyRepX1 and 2, as revealed by this study, hold promise for the development of innovative genetic engineering tools in cyanobacteria.